Strategy of the Election Supervisory Body (Bawaslu) in Preventing Violations in the 2019 General Election (Election) - Sri Roserdevi Nasution; Lidia Bernike; Mudir Johan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2020)
Election violations if they always occur have an impact on the integrity of Bawaslu as an election supervisory agency. Pekanbaru City Bawaslu must have a strategy and role to prevent, minimize and deal with election violations. The results of this research Bawaslu Pekanbaru City has carried out its role effectively through its strategies. The Pekanbaru City Bawaslu's strategy in the 2019 election is monitoring stalls, politicizing sara, monitoring posts and double data analysis. In dealing with violations in accordance with Law Number 7 of 2017 concerning Elections, Bawaslu is only authorized to make decisions on administrative violations carried out by the KPU. The obstacle for Bawaslu in carrying out its role is the inefficient budget and time in voting and collecting data on violations.